Respon Proliferasi, Diferensiasi dan Ekspresi C/EBPa Akibat Paparan Quercetin pada Kultur Preadiposit Tikus (Rattus Norvegicus) Strain Wistar Secara In Vitro - Retty Ratnawati; Satuman Satuman; Tinny Endang Hernowati (Research Journal of Life Science, 2015)
Introduction. Obesity is a metabolic syndrome as risk factor to the cardiovascular disease. Obesity occurs caused by adipocyte massive that is started by proliferation and differentiation of preadipocytes that involves transcription factors such as C/EBPα ,PPARγ and SREBP-1. Is known the TNF α and [Ca2+]i Increase when adiponectin decrease at the end of adipocyte differentiation. Therefore it is a deemed treat the obesity through the inhibition of adipocyte proliferation and differentiation using natural resources. Quercetin in due of the flavonoid found in apple,vegetables etc. The aim of this study is to prove the affectivity of quercetin to inhibit proliferation and differentiation of preadipocyte through inhibited of C/EBPα in rat preadipocytes culture method.Methods. Their study was a laboratory experimental. Quercetin was exposed to the preadipocytes human culture, after it was induced by differentiation stimulator the doses quercetin was grouped in: control, 50 µM (Q50), 125 µM (Q125) and 625 µM (Q625) groups. The amount of proliferation and differentiation was descriptive analyzed. The expression of C/EBPα, were identified by Immunocytochemistry and western blotting.Result. Quercetin 100 inhibited the rate of proliferation cell, while quersetin 625 inhibited differentiation in preadipocytes culture. There was a dose dependent to quersetin towards the decrease of PPARγ expression and C/EBPα expression in this preadipocytes culture.Conclusion. It is conclusion that quersetin inhibits proliferation and differentiation preadipocytes culture through the decrease of the expresion of C/EBP α.